STRATEGIC MANAGEMENT a roadmap for successful organizational transformation. - Bianchi Martini, Silvio; Corvino, Antonio; Dello Sbarba, Andrea ([S.l.] : ROUTLEDGE, 2024)
This book explores the intricate world of strategic management. Blending theory with practical examples, the authors provide a systematic framework for strategic decisionmaking. The book is divided into two parts. It begins by exploring the perspectives of strategic analysis, examining the firm's current situation and evolutionary perspectives, as well as the objective reality and subjective perspective. These interconnected perspectives require different analytical approaches to understand the firm's present state and the process of change. The second part, entitled The strategic map: the areas, the pathway and the objects of analysis, delves deeper into specific areas of strategic analysis. It focuses on the current state of the firm (today's firm), emphasizing the importance of understanding its resources, products, markets, activities, and stakeholder relationships. The quality and implementation effectiveness of the strategic model are also assessed, providing a reflection tool for improvement. The book further explores strategic change processes, the values and identity of the firm, performance evaluation, and corporate governance and internal control system. Suitable for newcomers and professionals in corporate strategy and governance, this book combines theory and practical examples to enhance understanding.
Keywords: Industrial management; Organizational change; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Development / Business Development